2022
DOI: 10.3389/fbioe.2021.798584
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of HOTAIRM1 as a Novel Biomarker for Oral Squamous Cell Carcinoma

Abstract: ORAL squamous cell carcinoma (OSCC) is a malignant tumor with the highest incidence among tumors involving the oral cavity maxillofacial region, and is notorious for its high recurrence and metastasis potential. Long non-coding RNAs (lncRNAs), which regulate the genesis and evolution of cancers, are potential prognostic biomarkers. This study identified HOTAIRM1 as a novel significantly upregulated lncRNA in OSCC, which is strongly associated with unfavorable prognosis of OSCC. Systematic bioinformatics analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…The lncRNA HOTAIRM1 has already been proposed as a biomarker for oral squamous cell carcinoma [28], and its role in the proliferation and metastasis of breast cancer has also been proposed [29]; the development of resistance to tamoxifen therapy due to the regulation of HOXA1 protein expression is being studied [30].…”
Section: Resultsmentioning
confidence: 99%
“…The lncRNA HOTAIRM1 has already been proposed as a biomarker for oral squamous cell carcinoma [28], and its role in the proliferation and metastasis of breast cancer has also been proposed [29]; the development of resistance to tamoxifen therapy due to the regulation of HOXA1 protein expression is being studied [30].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, higher miR-31 levels predicted nodal metastasis among stage I–III patients ( Tu et al, 2022 ). A close association between HOTAIRM1 and OSCC tumor development has been reported, with this lncRNA serving as a cell cycle regulator and candidate prognostic/therapeutic target in OSCC ( Yu et al, 2021 ). Higher LINC01793 levels are associated with a poorer OSCC prognosis for patients and poor clinicopathological features, showing that this lncRNA is an oncogenic mediator in cancer ( Yuan et al, 2021 ).…”
Section: Future Perspectives Of Lncrnas In Oral Squamous Cell Carcino...mentioning
confidence: 99%
“…Recently, growing evidence has suggested that HOTAIRM1 is an oncogene in multiple cancers and is important in tumorigenesis and development. It has been reported that HOTAIRM1 is upregulated in oral squamous cell carcinoma (OSCC) and enhances OSCC development 13 . HOTAIRM1 is highly expressed in glioblastoma multiforme (GBM) and is closely related to malignancy grade in GBM patients 14 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that HOTAIRM1 is upregulated in oral squamous cell carcinoma (OSCC) and enhances OSCC development. 13 HOTAIRM1 is highly expressed in glioblastoma multiforme (GBM) and is closely related to malignancy grade in GBM patients. 14 Ye et al demonstrated that HOTAIRM1 was involved in ovarian cancer (OV) development by upregulating MMP9 expression.…”
Section: Introductionmentioning
confidence: 99%